2014
DOI: 10.33670/18181023.v13i02.97
|View full text |Cite
|
Sign up to set email alerts
|

Características de la personalidad según el género en universitarios españoles

Abstract: En este artículo analizamos las diferencias de género de un grupo de estudiantes en relación a la personalidad, el optimismo y el afrontamiento al estrés, con el fin de conocer las características específicas de este colectivo en estas variables y si se mantienen las diferencias que apuntan otros estudios, lo cual permitirá proponer intervenciones específicas. En este estudio han participado 317 estudiantes universitarios, 51 varones y 266 mujeres, a los que se les aplicaron de forma individual diferentes inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, authors such as [54][55][56] found significant differences in favour of the male gender, with a small effect size (with Cohen's d between 0.22 and 0.477). Finally, other authors, such as Alvear [37,43,49,[57][58][59][60][61], found slightly higher mean scores in males, but the differences were not significant. Studies of gender differences in OM in university students therefore provide inconclusive data.…”
Section: Introductionmentioning
confidence: 73%
“…However, authors such as [54][55][56] found significant differences in favour of the male gender, with a small effect size (with Cohen's d between 0.22 and 0.477). Finally, other authors, such as Alvear [37,43,49,[57][58][59][60][61], found slightly higher mean scores in males, but the differences were not significant. Studies of gender differences in OM in university students therefore provide inconclusive data.…”
Section: Introductionmentioning
confidence: 73%